Exploring factors contributing to students satisfaction in blended learning environments: case of Universiti Kuala Lumpur Malaysia institute of information technology / Nadilah Mohd Ralim - Mohd Ralim, Nadilah (2016)
Blended learning was introduced to high education due to new advance in technology environments. Blended learning was mix-method of teaching learning between face-toface traditional methods and online learning activities that also called as flipped classroom. Blended learning has been implemented several years ago but due to the facilities provided is still underutilized. The objectives of this study is (1) to explore factor contributing to student satisfaction in blended learning environment in Universiti Kuala Lumpur Malaysia Institute of Information Technology (UniKL-MIIT). (2) To investigate the relationship of the factor contributing in student satisfaction in blended learning environment in Universiti Kuala Lumpur Malaysia Institute of Information Technology (UniKL-MIIT). (3) To provide recommendation to improve blended learning implementation in Universiti Kuala Lumpur Malaysia Institute of Information Technology (UniKL-MIIT). To achieve all three (3) objectives, methods of quantitative and qualitative are using to collect data from students and academicians. For students questionnaire they have to answer 35 questions based on five (5) constructs that evaluate the student's satisfaction in blended learning. These studies based from model of "Evaluating Student Satisfaction with Blended Learning in a Gender-Segregated Environment" that evaluates five (5) constructs are Interaction, Instruction, Instructor, Course Management and Technology adopted from Naaj, Nachouki, & Ankit, 2012 . Result and analysis show that all the relationship between five (5) construct was strong with positive results. The highest relationship was between Instructor and Interaction[r=.658 p<.0005 n=170]. The relationship analysis was interpret using Spearman's Rank Order Correlation. In this study also provide some recommendation in student satisfaction in blended learning environment.